3-D sketchup steel structural animation video / Mohd Firdaus Zainuddin ... [et al.] - Zainuddin, Mohd Firdaus; Lop, Nor Suzila; Zainal Abidin, Zaiwannizar (2024)
Colleges and universities have been using traditional approaches in teaching and learning using printed drawings and whiteboard hand sketches to understand construction drawings. These approaches may be good for students with good imaginary thinking but not for students lacking imaginary skills. The survey result focusing on the steel structural topic under Measurement of Construction Works IV (DQS251), shows that this topic has a low understanding level among the students if this topic is being lectured only by using printed and hand sketched drawings. Thus, 3-D SketchUp design software is used to create 3-D animations based on the previous examination question of the course on the selected topic of steel structure. The animation is then presented in class involving 58 students to increase the level of students’ understanding of steel structural drawing. After the video presentation session, positive perceptions and feedback from the students were obtained through questionnaires and reflective assessment. To conclude, the steel structural video animation has proven to enhance students’ understanding and visualisation skills on construction steel structural drawing and if designed properly will hopefully help to improve their understanding of drawing for this course.